Dampak Lingkaran Pertemanan Terhadap Proses Belajar Mahasiswa - Bambang Hermanto, Fajrin Muthia Muthohharoh; Azizah, Nur; Holihah, Mina; Anggraini, Diana Noor (Universitas Negeri Surabaya, 2023)
The purpose of students is to learn and complete their studies in preparing for a sustainable future. The quality of friendship can be found in the lecture environment while students undergo a learning process in completing their studies. The purpose of this study was to analyze the circle of peer association in UPI PIPS students class of 2020 on student learning outcomes during the lecture process. The method in this study uses qualitative methods. Data collection was carried out using purposive sampling techniques and then continued with snow ball sampling with the interview method, followed by 12 UPI PIPS student informants class of 2020. The results showed that positive friendship circles were important to support students, especially in deepening and execution of material, discussing , sharing important information, reminding each other's duties, and being an encouragement as difficult as any situation in the world of lectures. However, a circle of friendship can also have a negative impact, for example, carried away by hedonism, forgetting the purpose of studying, lazy to do the task, and feel alienated when in the middle of a friend who is not from the circle of their friendship. Thus, it can be concluded that a circle of friendship can be a factor that determines attitudes towards oneself and others, in adapting, seeking self -recognition, self -development, and enthusiasm for lectures. Keywords : social circle, student, self-development, social skillsT